Porous PLGA microparticles to encapsulate doxorubicin and polyethylenimine/miR-34a for inhibiting the proliferation and migration of lung cancer. Issue 99 (24th September 2015) - Wang, Chenhui; Wu, Di; Yang, Jiebing; Han, Haobo; Xing, Zhen; Zhang, Yan; Yang, Yan; Li, Quanshun
Abstract : Porous PLGA microparticles were successfully prepared for achieving the co-delivery of doxorubicin and PEI25K/miR-34a, using ammonium bicarbonate as a porogen. Abstract : Porous PLGA microparticles were successfully prepared for achieving the co-delivery of doxorubicin and PEI25K/miR-34a, using ammonium bicarbonate as a porogen. The synergistic effect between these two components ensured the efficient anti-proliferative and anti-migration effects of porous PLGA microparticles on tumor cells.